Maloklusi pada Penderita Cerebral Palsy - Virginia E. N. Abram; Sherly M. Gosal; Juliatri Juliatri (e-GiGi, 2023)
Cerebral palsy (CP) is a non-progressive disorder that affect the brain during the growth and development process. Various disorders in patients with cerebral palsy, such as dentocraniofacial and muscle abnormalities, can cause problems in dental and oral health, including malocclusion. The most common malocclusion described the patients with cerebral palsy is class II malocclusion with increased overjet and open bite. This literature review study aims to determine the classification and variation of malocclusion that occur in patients with cerebral palsy. This literature review research was conducted by searching for data using Google Scholar, Pubmed, and Science Direct databases. After being selected based on inclusion and exclusion criteria, a critical appraisal was carried out and 7 literatures were obtained. The result showed that Class II is the malocclusion that commonly occurs in patients with cerebral palsy, followed by Class I and Class III, with open bite as a common encounter malocclusion variant. In conclusion, the classification of malocclusion that occurs in patients with cerebral palsy is Class I, Class II and Class III. Generally, class II is the most common malocclusion in patients with cerebral palsy. Variations of malocclusion that occur in patients with cerebral palsy are open bite, crossbite, deep bite, crowding, spacing, a diastema, and increased overjet. The most prevalent variant is an open bite. Keywords: cerebral palsy, malocclusion   Abstrak: Cerebral palsy (CP) adalah gangguan atau kerusakan non-progresif pada otak saat proses pertumbuhan dan perkembangan. Berbagai gangguan pada penderita cerebral palsy, seperti kelainan pada dentokraniofasial dan ototnya, dapat menimbulkan masalah dalam kesehatan gigi dan mulut termasuk menyebabkan maloklusi. Maloklusi kelas II dengan peningkatan overjet dan open bite merupakan maloklusi yang sering terjadi pada penderita cerebral palsy. Penelitian literature review ini bertujuan untuk mengetahui klasifikasi dan variasi maloklusi yang terjadi pada penderita cerebral palsy. Penelitian dilakukan dengan pencarian data menggunakan database Google Scholar, Pubmed, dan Science Direct. Setelah diseleksi berdasarkan kriteria inklusi dan eksklusi, dilakukan critical appraisal dan didapatkan 7 literatur. Hasil penelitian menunjukkan bahwa maloklusi kelas II merupakan maloklusi yang umumnya terjadi pada penderita cerebral palsy diikuti dengan kelas I dan kelas III, dengan variasi maloklusi yang sering ditemukan yakni open bite. Kesimpulan penelitian ini yakni klasifikasi maloklusi yang terjadi pada penderita cerebral palsy yaitu maloklusi kelas I, kelas II dan kelas III, dengan maloklusi kelas II merupakan maloklusi yang paling umum terjadi pada penderita cerebral palsy. Variasi maloklusi yang terjadi pada penderita cerebral palsy yaitu open bite, cross bite, deep bite, crowding, spacing, diastema dan peningkatan overjet. Variasi maloklusi yang paling umum ditemui pada penderita cerebral palsy merupakan open bite. Kata kunci: cerebral palsy, maloklusi